Role of Ionizing Radiation in Neurodegenerative Diseases - Sharma, Neel K.; Sharma, Rupali; Mathur, Deepali; Sharad, Shashwat; Minhas, Gillipsie; Bhatia, Kulsajan; Anand, Akshay; Ghosh, Sanchita P. (Frontiers in Aging Neuroscience, 2018)
Ionizing radiation (IR) from terrestrial sources is continually an unprotected peril to human beings. However, the medical radiation and global radiation background are main contributors to human exposure and causes of radiation sickness. At high-dose exposures acute radiation sickness occurs, whereas chronic effects may persist for a number of years. Radiation can increase many circulatory, age related and neurodegenerative diseases. Neurodegenerative diseases occur a long time after exposure to radiation, as demonstrated in atomic bomb survivors, and are still controversial. This review discuss the role of IR in neurodegenerative diseases and proposes an association between neurodegenerative diseases and exposure to IR.